Lieux et pratiques de la plongée sous-marine sur la côte marseillaise : pour une approche géographique intégrée de l’espace marin littoral - Samuel Robert; Théophile Plouvier (VertigO, 2017)
Being a growing recreational activity on many coasts in the world, scuba diving is mainly known thanks to studies conducted in the frame of marine protected areas (MPAs). For management purposes indeed, it is necessary to know scuba diving practices and their ecological impact. But it is also important to report the socio-economic added value of this activity and thus the social utility of the environmental protection measures. Yet, as for many other recreational activities at sea, knowledge about scuba diving remain relatively incomplete and often unreliable. Furthermore, in the case of complex coastal zones, the geographical extent of the practices does not match systematically with the area of an MPA when it exists. It is therefore relevant to approach this activity at the level of the territorial system in which it occurs. This is the subject of this article which deals with the coast of Marseille (France), one of the world’s cradles of diving. Combining a large commercial port with various marine protected areas with distinct regulations, this coast is a prime but complex area for this activity. From a survey of key diving structures, a descriptive geography of scuba diving can then be revealed. It is then discussed with the management areas and the few efforts to organize the activity on the whole coast, from the integrated coastal area management perspective.